2015
DOI: 10.1155/2015/128653
|View full text |Cite
|
Sign up to set email alerts
|

α-2-Macroglobulin in Saliva Is Associated with Glycemic Control in Patients with Type 2 Diabetes Mellitus

Abstract: Background. Subjects with type 2 diabetes mellitus (DM2) require an adequate glycemic control to avoid diabetic complications. Currently, saliva biomarkers are used as a diagnostic tool and can be indicative of the degree of progression and control of various diseases. Several studies indicate that α-2-macroglobulin levels are elevated in diabetic patients. Methods. 120 subjects with DM2 were enrolled and classified into two groups according to their glycemic control (percentage of glycated hemoglobin-A1c (HbA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 23 publications
4
36
1
1
Order By: Relevance
“…A positive correlation was found between α-2-macroglobulin and HbA1c, which demonstrated that levels of α-2-macroglobulin in the saliva could reflect the glycaemic control in patients with type 2 diabetes mellitus. 25 However, the concentration of salivary melatonin decreased in patients with type 2 diabetes and patients with periodontitis. This indicates that salivary melatonin has an important role in the pathogenesis of diabetes and periodontal diseases, and might become a key biomarker in the diagnosis and treatment of these two diseases.…”
Section: Diagnosis Of Systematic Diseases By Salivamentioning
confidence: 99%
“…A positive correlation was found between α-2-macroglobulin and HbA1c, which demonstrated that levels of α-2-macroglobulin in the saliva could reflect the glycaemic control in patients with type 2 diabetes mellitus. 25 However, the concentration of salivary melatonin decreased in patients with type 2 diabetes and patients with periodontitis. This indicates that salivary melatonin has an important role in the pathogenesis of diabetes and periodontal diseases, and might become a key biomarker in the diagnosis and treatment of these two diseases.…”
Section: Diagnosis Of Systematic Diseases By Salivamentioning
confidence: 99%
“…It was showed by a proteomic evaluation that cell motility proteins-involved were up or down expressed in saliva from patients with DM versus controls (18). Higher levels of potassium and human α2-macroglobulin and lower expression of s-IgA and EGF secretion rates were also observed in diabetics when compared to healthy subjects by ELISA (19,20). It also has been demonstrated that animals diabetes-induced have important changes in the production of a several different extracellular matrix components and growth factors as TGFβ isoforms for example (8,21).…”
Section: Tgfβ1 In Diabetic and Hypertensive Patientsmentioning
confidence: 99%
“…Diabetes is a metabolic disease caused by lack of insulin secretion, insulin action or insulin resistance, which impairs the body's ability to process blood glucose. A positive association found between α-2-macroglobulin and HbA1c, demonstrated that levels of α-2-macroglobulin in the saliva could reflect the glycaemic control in patients with type 2 diabetes mellitus [30]. Type 1 diabetic hyperglycemia requires measuring exhaled methyl nitrate [31].…”
Section: Diabetesmentioning
confidence: 99%